Humor in Raza Ali Abidi’s Travelogues - Shah, Syed Waseem; Yousafzai, Altaf; Shah, Rabia (Makhz (Research Journal), 2023)
Raza Ali Abidi is a journalist, broadcaster, and travel writer, with six travelogues published to date. Although he has not formally engaged in humor writing nor published a specific book on the subject, his sense of humor makes him successful in the field of humor. This article examines the satire and humor present in his travelogues. Satire and humor are two distinct terms, and both are found in Raza Ali Abidi's works. In his humor, two aspects and objectives are evident. The first and primary objective is social reform, while the second is to enhance the liveliness of the writing. Along with humor, he uses satire to address collective social behaviors and attempts to bring about social reform. This article also presents a few examples from Raza Ali Abidi's travelogues. Undoubtedly, Raza Ali Abidi has succeeded in skillfully incorporating humor into his travelogues.